Analisis Framing terhadap Konten Dakwah Digital di Media Sosial Seperti Instagram @memeislam.id - Adhi Kusuma; Mad Nasir; Siti Nuraeni (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of digital technology has revolutionized how humans can communicate, including in Islamic preaching activities. Preaching, which used to be conventional, has now expanded into the digital realm through various social media platforms, one of which is Instagram. The @memeislam.id account has succeeded in implementing framing elements, namely defining problems, identifying causes, providing moral assessments, and offering solutions in conveying a message about Islam in a light, communicative, and contextual way. By combining humor, attractive visuals, and popular language, this account is able to create strong emotional resonance and encourage spiritual reflection among the audience. The success of this strategy is also shown by the high level of audience interaction in the form of reflective comments and emotional involvement.